A cell fate specification and transition mechanism for human foveolar cone subtype patterning - Katarzyna A. Hussey; Kiara C. Eldred; Brian Guy; Clayton P. Santiago; Jingliang Simon Zhang; Ian Glass; Thomas A. Reh; Seth Blackshaw; Loyal A. Goff; Robert J. Johnston (Proceedings of the National Academy of Sciences, 2026)
In the central region of the human retina, the high-acuity foveola is notable for its dense packing of green (M) and red (L) cones and absence of blue (S) cones. To identify mechanisms that pattern cones in the foveola, we examined human fetal retinas and differentiated retinal organoids. During development, sparse S-opsin-expressing cones are initially observed in the foveola. Later in fetal development, the foveola contains a mix of cones that either coexpress S- and M/L-opsins or exclusively express M/L-opsin. In adults, only M/L cones are present. Two signaling pathway regulators are highly and continuously expressed in the central retina: Cytochrome P450 26 subfamily A member 1 (CYP26A1), which degrades retinoic acid (RA) and Deiodinase 2 (DIO2), which promotes thyroid hormone (TH) signaling. Both CYP26A1 mutant organoids and high RA conditions increased the number of S cones and reduced the number of M/L cones in retinal organoids. In contrast, sustained TH signaling promoted the generation of M/L-opsin-expressing cones and induced M/L-opsin expression in S-opsin-expressing cones, showing that cone fate is plastic. Our data suggest that CYP26A1 degrades RA to specify M/L cones and limit S cones and that continuous DIO2 expression sustains high levels of TH to transition S-opsin-expressing cones into M/L cone fate, resulting in the foveola containing only M/L cones. Given the vulnerability of the foveola in macular degeneration and other retinal disorders, these findings provide a mechanistic framework for engineering organoids for therapeutic applications.